The prevention of work risks in the organization: proposal of a training programme - Alonso Morillejo, Enrique; Pozo Muñoz, Carmen; Hernández López, José Manuel (Apuntes de Psicología, 2022)
In view of the different standards that renew and update the context of work risk, training has become a crucial element for the development of a preventive culture and the reduction in the number of industrial accidents. Any training is aimed at the acquisition of certain abilities and knowledge. Due to all this, there is a need to carry out training schemes that can be implemented at different levels of the organization and that provide knowledge suitable for the application of the principles of prevention in the organizational context.